The value of n in the equation is 1
Step-by-step explanation:
The equation is [tex]-\frac{1}{2}[/tex] (2n + 4) + 6 = -9 + 4(2n + 1)
At first we must do that:
1. Open the brackets in both sides
2. Add like terms
3. Solve to find n
L.H.S:
∵ [tex]-\frac{1}{2}[/tex] (2n + 4) + 6 = -n - 2 + 6
∴ [tex]-\frac{1}{2}[/tex] (2n + 4) + 6 = -n + 4
R.H.S:
∵ -9 + 4(2n + 1) = -9 + 8n + 4
∴ -9 + 4(2n + 1) = 8n - 5
∴ -n + 4 = 8n - 5
- Add 5 to both sides
∴ -n + 9 = 8n
- Add n to both sides
∴ 9 = 9n
- Divide both sides by 9
∴ n = 1
The value of n in the equation is 1
Learn more:
You can learn more about equation in brainly.com/question/8955867
brainly.com/question/9738996
brainly.com/question/10708697
#LearnwithBrainly